Academic, socioeconomic and interpersonal consequences of cannabis use: a narrative review. (4th May 2022) - Castellanos-Ryan, Natalie; Morin, Élisabeth; Rioux, Charlie; London-Nadeau, Kira; Leblond, Maggy
Abstract: This article reviews the literature on the association between cannabis use (CU) and psychosocial functioning, operationalized here as academic achievement, economic prospects, social relationships and quality of life. So far, study results have been inconsistent. To clarify whether CU has an impact on psychosocial functioning, this article mainly reviewed prospective and longitudinal studies published since 2000 and examined whether studies controlled for confounding factors (e.g. socio-demographics, other substance use, psychopathology, social environment). The review suggested that when confounding variables are controlled for, the association between CU and psychosocial outcomes is generally small or non-significant. When significant associations remain, they are for chronic, dependent or early onset CU specifically, suggesting that the frequency of use and age of onset may be necessary elements to detect persistent, however small, psychosocial consequences. These results illustrate the importance of controlling for intra- and inter-individual differences to examine the link between CU and later psychosocial functioning. Results also suggest that policy and prevention efforts should consider targeting the individual and environmental factors (e.g. early academic and cognitive functioning, social disadvantage, family functioning, personality, smoking) that account for much of the association between CU and later psychosocial problems, rather than, or in addition to, CU itself.